Design and benchmark of an innovative concept to measure light charged particles in the R3B/FAIR experiment using RPCs - Miguel, Diogo André Afonso (2024)
Tese de Mestrado, Engenharia Física, 2024, Universidade de Lisboa, Faculdade de Ciências